2004
DOI: 10.1111/j.0143-2885.2004.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium hydroxide on physical and sealing properties of canal sealers

Abstract: Contact with Ca(OH)2 agents left on the canal wall caused considerable changes to the sealing ability of sealers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 15 publications
2
74
0
2
Order By: Relevance
“…It can be suggested that the influence of CH in the penetration of AH Plus could be more apparent in middle third, since the apical third has less dentinal tubules The lower sealer penetration in the apical third is also attributed to the ineffective delivery of irrigants and the reduced effectiveness of smear layer removal techniques in the apical region. CH removal is more difficult in the apical third; despite this, it interestingly did not have a role in the tubular penetration of both sealers in the 3-mm level segments (4,21).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It can be suggested that the influence of CH in the penetration of AH Plus could be more apparent in middle third, since the apical third has less dentinal tubules The lower sealer penetration in the apical third is also attributed to the ineffective delivery of irrigants and the reduced effectiveness of smear layer removal techniques in the apical region. CH removal is more difficult in the apical third; despite this, it interestingly did not have a role in the tubular penetration of both sealers in the 3-mm level segments (4,21).…”
Section: Discussionmentioning
confidence: 83%
“…Despite various proposed techniques, no technique thoroughly removes the CH dressing (4,21). The conventional syringe irrigation was used to remove the CH dressing before obturation procedures because this method does not require special devices, since the syringe is already used in root canal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CH placed inside a root canal must be completely removed before the latter can be filled with a permanent filling material. This is because CH residues on root canal walls reduce dentinal bond strength and compromise endodontic sealing by interfering with the penetration and adhesion of root canal sealers into dentinal tubules [4][5][6] . Several studies [7][8][9][10][11] have examined CH removal methods, and the most frequently described method is root canal instrumentation using a master apical file in combination with copious irrigation 7) .…”
Section: Introductionmentioning
confidence: 99%
“…6 Calcium hydroxide residues on the canal walls interfere negatively in endodontic treatment prognosis, 7 influence dentine bond strength, 8 affect the adhesion of the endodontic filling material to the root canal walls 9 and the penetration of sealers into dentinal tubules, 10 and react chemically with the sealer, interfering with its physical properties. 11,12 Several techniques have been proposed to remove the calcium hydroxide dressing from the root canal system, including the use of endodontic hand files, 13 sonic activation, 14 passive ultrasonic irrigation, 6,15 the CanalBrush System 6 and nickel-titanium rotary instruments. 16,17 Removal of the dressing using hand files, with or without an irrigating solution, may be inefficient and tedious, 6 whereas the use of NiTi rotary instruments may enhance the removal procedure when compared to the techniques Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%